Compromise and the Notwithstanding Clause: Why the Dominant Narrative Distorts Our Understanding - Hiebert, Janet L. (Contested Constitutionalism: Reflections on the Canadian Charter of Rights and Freedoms., 2023)
6 Compromise and the Notwithstanding Clause: Why the Dominant Narrative Distorts Our Understanding was published in Contested Constitutionalism on page 107.